Pengaruh Konsentrasi Nanokomposit SiO₂–TiO₂/PANI terhadap Morfologi Permukaan pada Kain Katun - Intan Puti Maharani; Ratnawulan, Ratnawulan (Journal of Science, Technology, and Innovation, 2025)
This study investigates the effect of SiO2–TiO2/PANI nanocomposite concentration on the surface morphology of cotton fabrics relevant to self-cleaning performance. A controlled laboratory experiment was conducted using four compositional ratios, while TiO2 content was fixed to isolate the structural role of SiO2 and PANI. Nanocomposites were synthesized via a sol–gel route, deposited by dip coating, and characterized using SEM combined with quantitative image analysis. The results demonstrate a systematic morphological evolution from relatively homogeneous, fine particle distributions to coarser and more agglomerated structures as PANI concentration decreased. Particle size distributions ranged predominantly between 40–90 nm, with higher PANI fractions promoting dispersion uniformity and reduced surface roughness. Increasing SiO2 dominance intensified particle growth and agglomeration, indicating altered interfacial interactions within the composite layer. Comparative analysis with prior studies confirms that oxide–polymer balance governs micro–nano architecture on textile substrates. These findings elucidate composition–structure relationships critical for optimizing functional textile coatings